THE LEXICAL-SEMANTIC FIELD ‘FAMILY’ IN THE RUSSIAN LANGUAGE - Jurayeva Janona Saidjon qizi (TADQIQOTLAR, 2026)
Abstract This article examines the lexical-semantic field “family” in the Russian language as an important fragment of the linguistic picture of the world. The study analyzes the structure of this field, its core and periphery, as well as the semantic relationships between the lexical units included in it. Particular attention is paid to the systemic relations within the field, including hyperonymy, synonymy, and derivational connections. The results of the research show that the lexical-semantic field “family” has a complex multi-level structure and reflects the cultural and social values of Russian society.